2008
DOI: 10.1590/s1806-37132008000500005
|View full text |Cite
|
Sign up to set email alerts
|

Efeitos da azatioprina sobre a depuração mucociliar após secção e anastomose brônquica em um modelo experimental em ratos

Abstract: Objective: To evaluate the effects of azathioprine on the mucociliary system in a model of bronchial section and anastomosis in rats. Methods: Thirty-six male Wistar-Furth rats were submitted to left bronchial section and anastomosis and divided into two groups to receive either saline solution or azathioprine. After 7, 15 and 30 days of treatment, six animals from each group were killed, after which in situ mucociliary transport velocity, in vitro mucus transportability, and contact angle of mucus in the righ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 14 publications
(12 reference statements)
0
2
0
1
Order By: Relevance
“…The mucociliary clearance was analyzed by the ciliary beating frequency (CBF) and the in situ mucociliary transport (MT), as described previously 9-12. Briefly, after the established ischemic period, the ventral wall of each tracheal segment was opened to expose the epithelium.…”
Section: Methodsmentioning
confidence: 99%
“…The mucociliary clearance was analyzed by the ciliary beating frequency (CBF) and the in situ mucociliary transport (MT), as described previously 9-12. Briefly, after the established ischemic period, the ventral wall of each tracheal segment was opened to expose the epithelium.…”
Section: Methodsmentioning
confidence: 99%
“…This impairment was attributed to alterations in mucus viscoelastic properties in the affected bronchial region. Another study demonstrated that azathioprine reduces the mucociliary transport velocity in animals evaluated 7 days after the surgical procedure (bronchial section and unilateral bronchial anastomosis), with animal recovery evaluated 30 days after surgery (11). Despite MCTV impairment, this study showed the improvement of mucus viscoelastic properties in animals undergoing bronchial section and bronchial anastomosis treated with azathioprine.…”
Section: Introductionmentioning
confidence: 99%
“…(entre 7 e 30 dias p = 0, 003; e entre 15 e 30 dias p = 0,005). Ainda dentro de estudos que avaliam apenas o procedimento cirúrgico e sua implicação dentro do aparelho mucociliar, citamos Marelli et al (1991) Em relação à velocidade de transporte in vivo (VTMC), Pazetti et al (2008) apresentaram diferença estatística no grupo submetido somente `a toracotomia esquerda que recebeu solução salina, pois este grupo apresentou uma melhora da VTMC no período de 30 a 90 dias ( p < 0, 001), demonstrando uma recuperação do aparelho mucociliar provocado pelo procedimento cirúrgico, o mesmo observado no grupo desta tese que foi submetido ao procedimento cirúrgico e recebeu solução salina no período entre 7 e 30 dias ( p = 0, 003) e 15 e 30 dias ( p = 0, 005), ou seja houve uma recuperação do aparelho mucociliar de ratos submetidos ao procedimento cirúrgico e que receberam solução salina. Pazetti et al (2008)…”
Section: Transportabilidade No Palato De Rã (Plt)unclassified